2004
DOI: 10.1063/1.1760598
|View full text |Cite
|
Sign up to set email alerts
|

Formation of titanium-solute clusters in alumina: A first-principles study

Abstract: Electronic structures and stability of substitutional Ti3+ clusters in Al2O3 were investigated by first-principles pseudopotential calculations using large supercells. It was found that a substitutional Ti3+ defect induces an extra defect level in the band gap, and the defect levels have strong bonding interactions in the cluster formation. In addition, binding energies of Ti3+ clusters increased with increasing numbers of Ti3+ ions, indicating that cluster formation is energetically favorable. The resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…We connect this discrepancy with the following. In [15] the band structure was calculated for the Ti 3+ Ti 3+ pair oriented along the [0001] axis while another orientation of that pair was implied in our calculations. The presence of Ti 3+ − Ti 4+ pairs ( Fig.…”
Section: Ti Impurity Levels In the Band Structurementioning
confidence: 99%
See 1 more Smart Citation
“…We connect this discrepancy with the following. In [15] the band structure was calculated for the Ti 3+ Ti 3+ pair oriented along the [0001] axis while another orientation of that pair was implied in our calculations. The presence of Ti 3+ − Ti 4+ pairs ( Fig.…”
Section: Ti Impurity Levels In the Band Structurementioning
confidence: 99%
“…In [15] the formation of Ti clusters in Ti-doped Al 2 O 3 was investigated. It was shown that Ti 3+ clusters have a positive binding energy.…”
Section: Introductionmentioning
confidence: 99%
“…Defect energetics in Ti:sapphire were investigated within the DFT approach in [14,15]. It was shown that in the oxidized conditions Ti 4+ ions substituted for Al 3+ ions together with charge compensating vacancies of Al (V 3− Al ) are the most stable defects.…”
Section: Introductionmentioning
confidence: 99%
“…24) Supercells containing a Zr impurity and an Al vacancy at different positions were calculated. The binding energy between the Zr impurity and the Al vacancy was estimated by the same method as a previous study 25) and the resulting binding energies were compared. Figure 3 shows the results of the calculated binding energies of the Al vacancy as a function of distance from the Zr site and the positional relationship between Zr and Al vacancy.…”
Section: Methodsmentioning
confidence: 99%